Development of a Measure of Postpartum PTSD: The City Birth Trauma Scale - Ayers, Susan; Wright, Daniel B.; Thornton, Alexandra (Frontiers in Psychiatry, 2018)
Posttraumatic stress disorder (PTSD) affects 4% of women after birth yet there are very few questionnaire measures of postpartum PTSD that have been validated in this population. In addition, none of the available questionnaires assess postpartum PTSD in accordance with criteria specified in the latest edition of the Diagnostic and Statistical Manual (DSM-5, 2013). The City Birth Trauma Scale is a 29-item questionnaire developed to measure birth-related PTSD according to DSM-5 criteria of: stressor criteria (A), symptoms of re-experiencing (B), avoidance (C), negative cognitions and mood (D), and hyperarousal (E), as well as duration of symptoms (F), significant distress or impairment (E), and exclusion criteria of other causes (H). Two additional items from DSM-IV were also included on the basis of evidence suggesting they might be important in this population. The first was criterion A2 that women responded to events during birth with intense fear, helplessness or horror. The second was symptoms of emotional numbing. Items were first reviewed by researchers (n = 9) and postpartum women (n = 8) and revised accordingly. The questionnaire was then completed by 950 women recruited online. Results showed the City Birth Trauma Scale had excellent reliability (Cronbach’s α = .92) and is easy to understand (Flesch reading score 64.17). Exploratory factor analysis found two factors which together accounted for 56% of the variance: (i) Birth-related symptoms (40.8% variance) and (ii) General symptoms (15.5% variance). PTSD symptoms were highly associated with distress, impaired functioning, and women reporting they wanted treatment (r = .50 - .61). Removing DSM-IV A2 criteria only increased births classified as traumatic by 2%. Adding the item on emotional numbing did not change the psychometric properties of the scale. These items were therefore removed. The City Birth Trauma Scale has good psychometric properties and the two symptom clusters identified are consistent with previous research on symptoms of postpartum PTSD. This scale therefore provides a promising measure of PTSD following childbirth that can be used in research and clinical practice. Future research should examine the scale’s predictive validity using clinical interviews.